Extremely Elevated Cerebrospinal Fluid Protein and Glucose Level in a Neonate with Hypernatremic Dehydration - Maria, Arti; Bandyopadhyay, Tapas (Journal of Pediatric Neurology, 2020)
We describe the case of a term newborn who presented with hypernatremic dehydration on day 19 of life. The baby was otherwise hemodynamically stable with no evidence of focal or asymmetric neurological signs. The laboratory tests at the time of admission were negative except for hypernatremia and the extremely elevated levels of cerebrospinal fluid (CSF) protein (717 mg/dL) and glucose levels (97 mg/dL). The hypernatremic dehydration was corrected as per the unit protocol over 48 hours. Repeat CSF analysis done after 5 days showed normalization of the protein and glucose levels. Serial follow-up and neuroimaging showed no evidence of neurological sequelae. Unique feature of our case is this is the first case reporting such an extreme elevation of CSF protein and glucose levels that have had no bearing on neurodevelopmental outcome at 1 month and 3 months of follow-up.
Keywords: hypernatremia; cerebrospinal fluid; extreme elevation